Regional hydrology heterogeneity and the response to climate and land surface changes in arid alpine basin, northwest China - Yang, Linshan; Feng, Qi; Yin, Zhenliang; Deo, Ravinesh C.; Wen, Xiaohu; Si, Jianhua; Liu, Wen (Catena (Giessen), 2020)
•The hydrology changes is sensitive to energy in high-altitude.•The hydrology changes is controlled by water limitation in low-altitude area.•The water-energy coupling relation highly relies on altitudinal gradient.•Climate change dominate the hydrological shifts in alpine region. Hydrology heterogeneity refers to the different water regimes or hydrological processes in response to heterogeneous in topography, landscapes, land cover, soil properties, geology and meteorology reflecting as the spatial variation of precipitation, evapotranspiration and water yield along with landscape, elevation, terrain and climate variation. However, the hydrology heterogeneity in the alpine region of inland river basin has remained unclear to date, which limits the understanding of the hydrology and landscape interaction mechanism and affects the rational utilization of regional water resources. In this study, we combined the soil and water assessment tool (SWAT) and water-energy coupling framework to detect the hydrology heterogeneity in the arid alpine region of Heihe River Basin (HRB). We applied SWAT model to present the hydrological processes and regimes at different landscapes and elevation bands by using field measured parameters, and investigate the hydrology heterogeneity as well as the response to the changes in recent climate and land surface in the perspective of water-energy coupling framework. The results indicate that SWAT is indeed a robust tool in representing the streamflow process in alpine region with accurate performance. The distribution of landscapes reflect the comprehensive effect of regional water-energy coupling, which highly rely on the altitudinal gradient. The hydrology heterogeneity in high-altitude area is sensitive to energy and in low-altitude area is sensitive to water limitation (drought stress). Climate change is the dominate factor that driving the hydrology heterogeneity shifts in alpine region of HRB, while, the effect of land surface change is gradually strengthening over the past 50 years, reflecting with the contribution of land surface change on hydrology shifts is gradually increasing.